2012
DOI: 10.1097/hjh.0b013e3283568158
|View full text |Cite
|
Sign up to set email alerts
|

Changes in prevalence, awareness, treatment and control of hypertension in Thai population, 2004–2009

Abstract: Despite improvement in awareness and control of hypertension in Thai population, a large proportion of hypertensive individuals remained suboptimally controlled. Strengthening measures to control high blood pressure and metabolic risk factors, especially obesity and hypercholesterolemia, in individuals with hypertension are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
56
1
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(68 citation statements)
references
References 16 publications
7
56
1
4
Order By: Relevance
“…Three measurements at intervals 2–5 minutes apart were obtained by using an automatic blood pressure monitor “Microlife BP-A100 model” (Microlife AG, Widnau, Switzerland) [16]. An average of the second and third values was used in the analysis [17]. …”
Section: Methodsmentioning
confidence: 99%
“…Three measurements at intervals 2–5 minutes apart were obtained by using an automatic blood pressure monitor “Microlife BP-A100 model” (Microlife AG, Widnau, Switzerland) [16]. An average of the second and third values was used in the analysis [17]. …”
Section: Methodsmentioning
confidence: 99%
“…4 We randomly selected the samples based on the four major geographic regions and the availability of the buffy coat samples in the samples bank in the Department of Medical Sciences, Ministry of Public Health, Thailand. In summary, 47 samples from the central, 47 samples from the North, 51 samples from the Northeast and 45 samples from the South were selected to perform DMETs genotyping.…”
Section: Population Samplesmentioning
confidence: 99%
“…In Thailand, hypertension is the third major risk factor associated with national disease burden and causing 600 000 DALY losses per year 4. The prevalence of hypertension has been estimated from a number of cross-sectional studies among adults and has been increasing over the past decades from 20% in 1985 to 22% in 2004 4–6.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of hypertension has been estimated from a number of cross-sectional studies among adults and has been increasing over the past decades from 20% in 1985 to 22% in 2004 4–6. The recent Thai National Health Examination Survey in 2009 reported that the prevalence of hypertension in adults was 21.5% 4. The emergence of hypertension has been the result of rapid socioeconomic development, which has resulted in one-third of Thais migrating to urban areas 7.…”
Section: Introductionmentioning
confidence: 99%